Thermogravimetric analysis on rice husk ashes-based geopolymer paste - Nasrudin, Nurul Reffa Azyan; Mazlan, Norkhairunnisa; Mohd Basri, Mohd Salahuddin; Mohamed Ariff, Azmah Hanim; Mohd. Nasir, Noor Azline (IOP Publishing, 2018)
Geopolymer is a material produced from the reaction of rice husk ashes and alkaline solution. These rice husk ashes are not widely used yet due to unstable chemical content than fly ashes. However, the high Si content in rice husk ashes are believed to contribute for better thermal properties such as in coating application. This paper will discuss the studies done to rice husk ashes geopolymer in aspects of thermal stability via conducting thermogravimetric analysis. Thermogravimetric analysis is carried out to determine the optimum temperature for each sample. This work shows the reactions of geopolymer paste with different molarity of NaOH solutions.